Endoscopic Saphenous Vein Harvesting and Surgical Site Infections after Coronary Artery Bypass Surgery (CABG) - Muhammad Arsalan Ali, Muhammad Ahmed, Hamad Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Coronary artery bypass grafting (CABG) surgery remains the most common procedure in adult cardiac surgery for coronary artery disease. Objectives: The main objective of the study is to find the infection in open vs endoscopic saphenous vein harvest for patients undergoing CABG surgery. Material and method: This comparative analysis was conducted at Rawalpindi Institute of Cardiology, Armed Forces Institute of Cardiology, Rawalpindi and Shifa International Hospital, Islamabad from October 2019 to 2021. The data was collected with the permission of the ethical committee of hospital. The data was collected with the permission of the ethical committee of the hospital. Patients undergoing CABG or combined valve/CABG with EVH and OVH were differentiated from each other in the MHCCSR as of the start of the study period. The OVH was performed by either a continuous, longitudinal incision or through multiple smaller incisions. Results: The data were collected from 122 patients, from these 22 patients were not extubated and none of them survived. The most common indication for surgery was myocardial revascularization (30.6%), followed by valve replacement (22.7%) and thoracic aortic aneurysm repair. Practical implication: EVH is now considered not to be the best method in CABG surgery. Conclusion: It is concluded that, patients undergoing CABG surgery with EVH presented with worse systolic function and more recent myocardial infarction. Keywords: CABG, Procedure, EVH, Systolic, Myocardial infarction, Endoscopic